2019
DOI: 10.1016/j.ejogrb.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Consent in pregnancy: A qualitative study of the views and experiences of women and their healthcare professionals

Abstract: Objective: Consent in antenatal settings is contentious, poorly understood and recognised as problematic for pregnant women. This study aimed to investigate participants' views and experiences of the consent process. Design: Qualitative research performed in a large urban teaching hospital in London. Sixteen pregnant women and fifteen healthcare professionals (obstetricians and midwives) participated. Consent consultations were observed and in-depth interviews carried out with healthcare professionals and preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
4
14
0
Order By: Relevance
“…In line with studies in other settings, a signi cant nding of our study is that six out of ten women wanted to be asked on the birth preference (11,28,29), which reinforces the need to tailor the design and content of interventions targeting women and con rms women's desire for communication and an informed dialogue with healthcare providers (30).…”
Section: Discussionsupporting
confidence: 81%
“…In line with studies in other settings, a signi cant nding of our study is that six out of ten women wanted to be asked on the birth preference (11,28,29), which reinforces the need to tailor the design and content of interventions targeting women and con rms women's desire for communication and an informed dialogue with healthcare providers (30).…”
Section: Discussionsupporting
confidence: 81%
“…In line with studies in other settings, the significant finding of our study is that six out of ten women would have wanted to be asked about birth preference (27)(28)(29). The message reinforces the need to tailor interventions targeting women so as to include them as an active participant in health care decisions and confirms women's expectations for communication and informed dialogue with healthcare providers (30).…”
Section: Discussionsupporting
confidence: 80%
“…Again, patient-provider communication was listed as an important variable in mitigating healthcare disparities. Building on communication, Nicholls et al [28] utilized an interpretive qualitative methodology and found women in their perinatal periods could benefit from an empowering approach, where they feel like they are able to make choices about their bodies and their pregnancies. Further, a woman-first healthcare initiative could be advantageous, as opposed to the usual compliance culture within healthcare settings [28].…”
Section: Peri-partum Factorsmentioning
confidence: 99%